2018
DOI: 10.1049/iet-nbt.2018.0057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticles and silver nitrate on growth of rice under biotic stress

Abstract: This study was organised to check the effect of silver nanoparticles and silver nitrate on rice growth against biotic stress. Silver nanoparticles were synthesised by using plant extract as reducing agent, followed by characterisation through UV Vis spectroscopy, XRD, EDS and SEM. Aspergillus application significantly reduced rice plant fresh mass (0.9%), dry mass (0.21%), root length (2.3%), shoot length (5.2%) and root number (1%) in comparison to control. Similarly, leaf area, leaf fresh mass, dry mass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 42 publications
(46 reference statements)
3
13
0
Order By: Relevance
“…Stampoulis et al demonstrated that AgNPs (>100 mg/L) inhibited seed germination and reduced biomass in zucchini (Cucurbita pepo ) [54]. Similar results regarding the toxicity on seed germination, biomass accumulation, and root and shoot growth by AgNPs were reported in other studies involving various plant species, including Arabidopsis [55], Brassica nigra [56], Lemna [57], Phaseolus radiatus and Sorghum bicolor [58], Lolium multiflorum [59], rice [60], wheat [61], Lupinus termis L. [62], and so on. A summary of compiled descriptions of the effects of AgNPs in plants is shown in Table 1.…”
Section: Phytotoxicity Of Agnpssupporting
confidence: 67%
“…Stampoulis et al demonstrated that AgNPs (>100 mg/L) inhibited seed germination and reduced biomass in zucchini (Cucurbita pepo ) [54]. Similar results regarding the toxicity on seed germination, biomass accumulation, and root and shoot growth by AgNPs were reported in other studies involving various plant species, including Arabidopsis [55], Brassica nigra [56], Lemna [57], Phaseolus radiatus and Sorghum bicolor [58], Lolium multiflorum [59], rice [60], wheat [61], Lupinus termis L. [62], and so on. A summary of compiled descriptions of the effects of AgNPs in plants is shown in Table 1.…”
Section: Phytotoxicity Of Agnpssupporting
confidence: 67%
“…In our experimental set-up, we also saw a negative effect of ABA on shoot and root growths, also in agreement with previous work [90]. Finally, we observed a significant increase in seminal root length upon treatment with the ethylene perception inhibitor AgNO 3 , also corresponding to previous findings [91]. An ACC treatment had been found to significantly increase the shoot and decrease the root [92], but in our experiment, the length of total shoot had significantly increased, but that of the internode and the root did not differ significantly.…”
Section: Methods Validationsupporting
confidence: 93%
“…Overall, longitudinal growth of roots and shoots as well as increased leaf area could be attributed to the effect of AgNO 3 . These results are consistent with those reported by other researchers regarding increased shoot and root length and leaf area Alva Ticona and Oropeza, 2013;Tamimi, 2015;Taha and Hassan, 2016;Ejaz et al, 2018). In addition to the inhibitory effect of silver ions on ethylene and growth stimulation, nitrate as the main source of nitrogen and interference in the structure of amino acids and nucleic acids, is one of the growth factors in plants (O'Brien et al, 2016;Hachiya and Sakakibara, 2016;Sun et al, 2017) leading to longitudinal growth of roots and shoots and increased leaf area.…”
Section: Effect Of Agno3 On Growth Parameterssupporting
confidence: 93%